Collaborative Activities in the Learning of Discourse Markers in University Students - Villar Revello, Erika María Villar Revello (2018)
The objective of this research work is to analyze the influence of collaborative activities on the learning of discourse markers in the students of the Language Comprehension and Production from a private university in Lima. It is an applied research with a quasi-experimental design, composed of experimental and control. For the collection of data, the Test on discourse markers was used. Likewise, a pretest measurement was carried out successively, and once the results were obtained, the workshop on collaborative activities, composed of 7 sessions, was conducted in the experimental group to then carry out the posttest measurements in both groups. The hypothesis testing was made with the Mann Whitney U test. The results showed that there was significant influence of the collaborative work on the learning of the discourse markers in the students that are object of study.